Polyol esters as thinner and biolubricant additive for synthetic-based drilling fluid - Kania, Dina (2019)
Drilling fluids are designed to clean the well, cool and lubricate the drilling tools, and maintain the stability of the wellbore. Recently, there is a demand to increase the lubricity of synthetic-based drilling mud (SBM) to prolong the life of drill strings, but the availability of lubricants for SBM is still very limited. There is also limited chemical thinners available in the market for SBM. Non-ionic polyol esters have not been applied in SBM despite their potential in lubricating and viscosity thinning purposes. The knowledge of the impact of polyol esters on SBM is important to study thoroughly prior to application in drilling fluids. Therefore, the performance of palm oil-based polyol esters as multifunctional non-ionic thinners and lubricity enhancers in SBM was investigated in this study through experimental and computational molecular approach. Three types of polyol esters, namely pentaerythritol ester (PEE), trimethylolpropane ester (TMPE), and neopentyl glycol ester (NPGE), were selected for the analysis. Tribological investigation showed that polyol esters significantly reduced the coefficient of friction (COF) of SBM by 22% at a concentration of 1% due to adsorption of polar molecules of polyol ester on the metal surfaces (boundary lubrication). However, only PEE and TMPE reduced the scar diameter by 30% at a concentration of 3% due to triester and tetraester content. The presence of polyol ester was observed on mud cake as an increase in carbon content from 25.68% to 40.92%, resulting in a more compact mud cake and filtrate reduction by 45.5%. This can contribute to a more lubricious mud cake. Rheological evaluation showed that polyol esters exhibited a substantial reduction of rheology, particularly yield point, after a simulated drilling temperature of 275°F for 16 hr. Non-ionic polyol esters worked by separating and encapsulating the organoclay in the mud, causing the steric repulsion and stabilization of the organoclay. PEE produced the most controllable rheology: at concentrations of 1, 2, 3% PEE reduced the yield point by 20, 26, and 58%, respectively. From rheology model fitting, it was found that the rheology of SBM with polyol ester were best described by Herschel-Bulkley model.